2020
DOI: 10.1186/s12888-020-02520-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric properties of the perceived stress scale in a community sample of Chinese

Abstract: Background: The Perceived Stress Scale (PSS) is a globally used and self-report scale measuring perceived stress. Three versions of PSS (PSS-14, PSS-10 and PSS-4) are available which comprise 14, 10 and 4 items respectively. However, the Chinese version of the PSS has not yet been validated in a large community-based general population. The aims of this study were to evaluate the psychometric properties of the Chinese PSS in a large community-based general population and to compare the appropriateness of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 31 publications
4
108
0
2
Order By: Relevance
“…Our overall mean score (19.08, SD = 7.17) was higher than what was preliminarily reported in Limcaoco et al, 2020 (17.40, SD = 6.40)—a global survey that ended on 1 April 2020. Reported PSS-10 norms prior to the pandemic showed an average score of 12.89 in Germany, 15.81 in Mexico, 19.25 in India, 19.2 in China, 19.79 in UK, and 15.05 in the US [ 46 , 47 , 48 , 49 , 50 , 51 ]. Compared to normative PSS-10 data, our means showed an overall trend of higher averages in the country-level analyses we report (e.g., Germany and Mexico; we were unable to find pre-pandemic PSS-10 data for Pakistan) [ 12 , 47 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our overall mean score (19.08, SD = 7.17) was higher than what was preliminarily reported in Limcaoco et al, 2020 (17.40, SD = 6.40)—a global survey that ended on 1 April 2020. Reported PSS-10 norms prior to the pandemic showed an average score of 12.89 in Germany, 15.81 in Mexico, 19.25 in India, 19.2 in China, 19.79 in UK, and 15.05 in the US [ 46 , 47 , 48 , 49 , 50 , 51 ]. Compared to normative PSS-10 data, our means showed an overall trend of higher averages in the country-level analyses we report (e.g., Germany and Mexico; we were unable to find pre-pandemic PSS-10 data for Pakistan) [ 12 , 47 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological stress —Psychological stress was measured by the Chinese version Perceived Stress-10 Scale (PSS-10), including 6 negative and 4 positive items. Each item is rated on a 5-point Likert-type scale, ranging from 0 (never) to 4 (very often) ( Huang et al, 2020 ). Therefore, the score of PSS-10 ranges from 0 to 40.…”
Section: Methodsmentioning
confidence: 99%
“…18 years; education ! junior high school; [43]). PSS assesses the extent that individuals believe their lives are overloaded, unpredictable, and uncontrollable (eg, in the last month, how often have you found that you could not cope with all the things that you had to do?).…”
Section: Participantsmentioning
confidence: 99%